PROBLEMS AND SOLUTIONS IN TEACHING FOREIGN LANGUAGES - Rustamov, Abdushukur (Журнал иностранных языков и лингвистики, 2023)
The process of globalization requires people to learn several foreign languages ​​in addition to their mother tongue. Current research shows that starting this process at an early age is more effective. In our country, strict attention is paid to this issue, programs are being developed based on a new approach to teaching foreign languages, especially English, in cooperation with the world’s leading organizations and universities. Large-scale projects on teaching English are being implemented in state-owned and private educational institutions.